Evaluation of Productive and Nutritional Parameters for the Use of Lactobacillus acidophilus and Lactobacillus bifidusin the Diet of the Golden Hamster (Mesocricetus auratus) - Corredor , José Ricardo; Hernández, Cristina; Arias, Andrés (Spei Domus, 2014)
Introduction: many authors have regarded probiotics as microorganisms that are beneficial for gut flora, working through various mechanisms and with effects reported not only in the gastro-intestinal tract but also in the respiratory and urogenital tracts. The aim of this study was to evaluate productive parameters (growth and weigh gain) and nutritional parameters (fecal content of nitrogen, fat, ash and moisture) against the supply of a commercially used probiotic cocktail containing Lactobacillus acidophilus and Lactobacillus bifidus in the golden hamster. Materials and methods: we selected 20 experimental animals with an average age between 8 and 15 days. These were then divided into two experimental groups: control (GCJ) and experimental (GMS). Each week for 3 weeks we measured weight (grams) and length (centimeters) variables, and conducted a proximate analysis of feces to determine the nitrogen, fat, ash and moisture content. Data were expressed in ± SD averages for the variables of growth and weight gain. Results: the results obtained showed that administering the probiotic significantly affected weight gain and growth, reduced fecal excretion of nitrogen (interpreted as better digestion and absorption of proteins), reduced ash elimination, and increased fecal excretion of fat, which was largely attributed to an excess of this nutrient in the diet provided. Conclusions: the use of probiotics is an extremely useful tool that can be used in production systems to replace other products that may generate public health risks.